Edukasi "Isi Piringku" Meningkatkan Kemampuan Menyajikan Menu Seimbang pada Orang Tua Anak Usia Prasekolah - Zulkarnaini Zulkarnaini; Iba Supra Saba (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Background: Parents play an essential role in establishing healthy eating habits among preschool children. Limited understanding of the My Plate ("Isi Piringku") guidelines may affect parents' ability to prepare balanced meals for their children. Objective: To analyze the effect of My Plate ("Isi Piringku") education on parents' ability to prepare balanced meals for preschool children at TK Meunasah Intan, Aceh Besar. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. The participants were parents of preschool children at TK Meunasah Intan, Aceh Besar, selected using purposive sampling. The intervention consisted of My Plate ("Isi Piringku") education, while parents' ability to prepare balanced meals was assessed before and after the intervention using an observation checklist. Data were analyzed using the Paired t-test or the Wilcoxon Signed-Rank Test with a significance level of p < 0.05. Results: My Plate ("Isi Piringku") education improved parents' ability to prepare balanced meals, as indicated by higher post-intervention scores with a statistically significant difference (p < 0.05). Conclusion: My Plate ("Isi Piringku") education is effective in improving parents' ability to prepare balanced meals for preschool children at TK Meunasah Intan, Aceh Besar.